Man Is Like a Fruit Tree - Bobst, Elmer Holmes (Tufts Archival Research Center, 2006)
Elmer Bobst, President of Warner-Hudnut Incorporated, describes his 82-year-old friend Bernard Baruch, and describes his belief that long life and happiness are achieved through the act of remaining productive, even after retirement.